In Vitro Conservation of Withania Somnifera (L) Dunal (Ashwagandha) - A Multipurpose Medicinal Plant - Kumar, O. Aniel; Jyothirmayee, G; Tata, S. Subba (Journal of Asian Scientific Research, 2013)
Present work has been conducted on In Vitro conservation of a multipurpose medicinal plant, Withania somnifera commonly known as Ashwagandha through storage of germplasm derived from micropropagated progenies of the species. Direct regeneration of cotyledon explants and their multiplication have been optimized using cytokinins (BAP and KIN) at a concentrations of 0.5-3.0mg/l alone, BAP+KIN combined forms and combined with auxins (IAA and NAA) at 1.5mg/l and 2.0mg/l. MS medium supplemented with BAP(2.0mg/l) and IAA(1.5mg/l) produced maximum number of shoots per explant i.e., 57.4±0.59 and 50.0±0.40 were recorded from Withania somnifera WS1 and WS2 cultivars respectively. An improved In Vitro shoot bud elongation was achieved on MS medium fortified with 0.15mg/l GA3. High frequency of rooting 64% and 60.1% and maximum number of 12.8±0.16 and 10.6±0.49 roots were produced on MS medium supplemented with IBA(5mg/l) in WS1 and WS2 respectively. After acclimatization, 85% of the micropropagated plantlets were successfully established in the field.